Teknik Mengatasi Layu Pada Tanaman Cabai Menuju Desa Sejahtera Mandiri Di Kelompok Tani Desa Padang Mutung Kecamatan Kampar - Ardian Ardian; Murniati Murniati; Sri Yoseva; Elza Zuhri; Nurbaiti Nurbaiti (Unri Conference Series: Community Engagement, 2021)
The need for chili peppers (Capsicum annuum L.) in Riau Province increased, along with the increasing population, while production in 2019 of 17,513 tons has not been able to meet the needs, so it was imported from other provinces such as, West Sumatra, North Sumatra, and other provinces. If there is a shortage of supply such as a broken road to Riau, or low production it will have an impact on increasing chili prices in Riau, for that it is necessary to increase chili production in Riau. Farmers in farming chili, often experience crop failure due, one of which is high infection withered fusarium disease caused by the fungus Fusarium oxysporum f.sp. capsici. This fungus develops quickly in soil conditions with high humidity, especially during harvest that coincides with the rainy season, where transmission is carried out by spores mainly through the intercession of water flow in roots and leaves (Heriyanto, 2019). The purpose of this community service is to improve the knowledge and skills of farmers in overcoming withers in chili plants. Devotional activities are held in April - October 2021, in the form of lectures and discussions and the creation of pilot pilot pilots. As a result of the service, the community understands the technique of planting and overcoming withers in chili plants.